Designing a successful library school field experience - Kelsey, Paul; Ramaswamy, Mohan (My University, 2005)
To share the library school field experience paradigm that the authors developed after their successful participation as a supervisor and student. Design/methodology/approach – A review of field experience literature is provided. The field experience paradigms and perspectives pertaining to the supervisor and the student are explained. The paradigm is suggested as a model for field experience participants and their supervisors. Findings – The field experience paradigm for the supervisors elucidates the stages – planning, training, mentoring and evaluation. The paradigm for students explains the phases – awareness, interests, planning and participation. Research limitations/implications – The focus of the field experience, from which the paradigm emanated, was to train and prepare the student for agricultural librarianship in an academic library. The application of the paradigm may vary for different situations. Practical implications – The paradigm is expected to be useful for supervisors and students of field experience programs. Originality/value – This paradigm stems from the participation of the authors as a field experience supervisor and student. The steps and methods the authors followed will help advance future field experience programs.
Keywords: Practicum; Internship; Field experience; On the job training; Career development; Shadowing; Librarians; Recruitment